A study of the motives of perpetrators of sexual violence against children (case study of 5 perpetrators ff sexual violence in the special institution for children class I Medan) - Erni Asneli Asbi; Tasya Novriyanti (Goodwood Publishing, 2025)
Purpose: To determine the motives of perpetrators of sexual violence against children in the immediate environment and how the modus operandi is carried out by the perpetrators. Research Methodology: This research employed a qualitative approach with a case study method involving five perpetrators of child sexual violence detained at the Class I Special Institution for Children (LPKA) in Medan. Data were collected through in-depth interviews, observations, and documentation to uncover the underlying motives and behavioral patterns. Results: The results of the study indicate that there is a superior position and interior between the perpetrator and the victim, where the perpetrator feels more powerful than the victim, triggering the occurrence of sexual violence. The existence of motives in the past (because motive), such as having a bad experience in the past that causes a sense of resentment, and all informants lacking early socialization from their families in the past, especially in understanding religion. Motives in the present (in order to motive), namely reasons delivered by the perpetrator, such as miscommunication. Conclusions: This study concludes that sexual violence is not merely a result of individual deviance but is also shaped by weak social control, poor family communication, and negative peer environments. The opportunities and accessibility of pornographic content further exacerbate these behaviors. Limitations: This study focused only on five perpetrators in one institution, without incorporating victims’ perspectives or broader socioeconomic contexts, limiting generalizability. Contribution: This research enriches sociological discourse on social welfare and child protection, offering insights for families, communities, and policymakers to strengthen preventive measures, social control, and rehabilitation programs.